A Note On Wh-Questions In Avatime - Devlin, Kerri; Lehman, Blake; MAJOR, TRAVIS; Torrence, Harold (My University, 2021)
This paper examines wh-question constructions in Avatime, an endangered Ghana Togo Mountain language. We focus on the different wh-strategies and island constraints and discuss these in relation to left peripheral elements such as question particles and complementizers.
Keywords: wh-question constructions; Avatime; endangered